Educated Girls, Absent Grooms, and Runaway Brides: Narrating Social Change in Rural Bangladesh - Roslyn Fraser Schoen (Forum: Qualitative Social Research, 2015)
This article explores the folk legend as one articulation of the social control of women in rural Bangladesh. Stories and legends emerged when women were interviewed about the effects of men leaving the village for wage-based jobs in cities and abroad. Interviews were analyzed via immersion, theme generation, and open coding (MARSHALL & ROSSMAN, 2006) with a focus on women's own narratives and meaning-making, which allowed for these stories to be understood as significant components of people's everyday realities (GUBRIUM & HOLSTEIN, 2009). These stories are consistent with GOLDSTEIN's (2004) definition of a legend: they are not personal stories yet they are not completely impersonal (friend-of-a-friend subject), they take on a believe-it-or-not tone, and telling them presents minimal risk to the narrator. Like other folk legends, these stories act as a means to reinforce the social order during a time of social change. As other research has shown (COONTZ, 1999; COOPER, LINSTROTH & CHAITLIN, 2009; GREENE, 1991; MADRIZ, 1997), stories as social control mechanisms focus specifically and uniquely on women during times of social change. Respondents discuss "accidents" and "scandals" that occur when women do not adhere to marriage customs or the traditional dichotomy of public and domestic spheres.